Calibration method for flap structure of macrofluidic airflow sensor - Yusoff, Mohd Hanafiah; Abdullah, Sukarnur Che; Nasser, Nasraan Shah Mohamed; Amari, Mohd Dzulhelmy (2023)
The calibration method for flap structure of microfluidic airflow sensor is explained in this paper. Many related studies regarding developing the hardware of the system such as high sensitivity of the airflow sensor in detecting the changes either in user or in the environment. The effects of the fast detection of the sensor through the high sensitivity of the airflow sensor have enabled the system to identify and analyze the behavior of the user with higher accuracy compared to the conventional system. In this study, the accuracy of the sensor to react based on the situation is still a problem to the inventor and the developer where more boundary condition needs to insert in the commands to have the sensor to function more accurate. By using ANSYS, MPLAB X IDE, and Pareto Optimality Analysis, the calibration method for a new airflow sensor system can be identified and analyze the performance of the user in higher reliability compared to a common system. This technical paper focused on determines and calibrate the small changes of the airflow motion for a low and high relative velocity of the new dynamic airflow sensor. The results exhibit high accuracy for the detection structure in sensing the airflow changes from the surroundings.